DEVELOPMENT AND VALIDATION OF ANALYTICAL METHOD FOR PALM OIL DETERMINATION IN MICROCAPSULES PRODUCED BY COMPLEX COACERVATION - Marfil, Paulo H. M. [UNESP]; Vasconcelos, Felipe H. T.; Pontieri, Marcia H.; Telis, Vania R. N. [UNESP] (Soc Brasileira Quimica, 2016)
The microencapsulation of palm oil may be a mechanism for protecting and promoting the controlled release of its bioactive compounds. To optimize the microencapsulation process, it is necessary to accurately quantify the palm oil present both external and internal to the microcapsules. In this study, we developed and validated a spectrophotometric method to determine the microencapsulation efficiency of palm oil by complex coacervation. We used gelatin and gum arabic (1:1) as wall material in a 5% concentration (w/v) and palm oil in the same concentration. The coacervates were obtained at pH 4.0 +/- 0.01, decanted for 24 h, frozen (-40 degrees C), and lyophilized for 72 h. Morphological analyzes were then performed. We standardized the extraction of the external palm oil through five successive washes with an organic solvent. We then explored the best method for rupturing the microcapsules. After successive extractions with hexane, we determined the amount of palm oil contained in the microcapsules using a spectrophotometer. The proposed method was shown to be of low cost, fast, and easy to implement. In addition, in the validation step, we confirmed the method to be safe and reliable, as it proved to be specific, accurate, precise, and robust.
Keywords: palm oil; encapsulation; spectrophotometry; gelatin; gum arabic